2018
DOI: 10.1021/acs.jpca.8b09410
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Water Wires to Bifurcated H-Bond Networks in 2-Pyridone·(H2O)n, n = 1–4 Clusters

Abstract: Mass-selective two-color resonant two-photon ionization (2C-R2PI), UV/UV hole-burning, and infrared (IR) depletion spectra of supersonic jet-cooled 2-pyridone·(H2O) n clusters with n = 1–4 have been measured to investigate the local hydration patterns around 2-pyridone (2PY) as a function of cluster size. As shown by others, the IR frequencies of the OH and NH stretches of the n = 1, 2 clusters are characteristic of water wires stretching from the NH to the CO group of 2PY. We identify two isomers (3A and 3B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 57 publications
(131 reference statements)
1
12
0
2
Order By: Relevance
“…In 2013, Leutwyler and co-workers measured the vibrational spectra of 2PY-(NH 3 ) n in the NH and CH stretch fundamental region (2400–3700 cm –1 ) using infrared (IR) laser depletion spectroscopy for n = 1–3 . In 2018, Leutwyler and co-workers measured the vibrational spectra of 2PY-(H 2 O) n for n = 3 and 4 with an emphasis on the IR signatures of the different H-bond structural motifs using mass- and isomer-specific two-color resonant two-photon ionization for cluster size and isomer identification …”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In 2013, Leutwyler and co-workers measured the vibrational spectra of 2PY-(NH 3 ) n in the NH and CH stretch fundamental region (2400–3700 cm –1 ) using infrared (IR) laser depletion spectroscopy for n = 1–3 . In 2018, Leutwyler and co-workers measured the vibrational spectra of 2PY-(H 2 O) n for n = 3 and 4 with an emphasis on the IR signatures of the different H-bond structural motifs using mass- and isomer-specific two-color resonant two-photon ionization for cluster size and isomer identification …”
Section: Introductionsupporting
confidence: 80%
“…16 In 2018, Leutwyler and co-workers measured the vibrational spectra of 2PY-(H 2 O) n for n = 3 and 4 with an emphasis on the IR signatures of the different H-bond structural motifs using mass-and isomer-specific two-color resonant two-photon ionization for cluster size and isomer identification. 17 When 2PY is solvated by water, methanol, or ammonia molecules, it is not surprising to see the complex vibrational spectra at 3 μm as a result of formation of hydrogen-bond networks. For example, Zwier and co-workers have analyzed the spectra of 2PY-(H 2 O) 1 and 2HP-(H 2 O) 3 and speculated the origin of their complex vibrational features at 3 μm to be (1) the existence of multiple conformers, (2) H-atom transfer, and (3) inherent anharmonic coupling in water hydrogen-bond networks.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Herein we tried to explain such aromatic behavior of 2PY analogs surrounded by water molecules through H-bonded network. Recent work from Leutwyler's group [30] discussed the evolution of water cluster (n = to 4) around 2-pyridone moiety. With the help of supersonic jet-cooled gas-phase spectroscopy and quantum calculations, the authors concluded that clusters with one and two water molecules are characteristics of sequential H-bonded water-wires.…”
Section: Probing Aromaticity Of 2py 2tpy and 2sepy In A H-bonding Smentioning
confidence: 99%
“…Gambar 1. Fishbone Perak Sulfat (Ag2SO4) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Penelitian dilakukan dalam beberapa tahapan, yaitu (1) Analisis 2D molekul Ag2SO4 secara dua dimensi menggunakan ChemDraw 2D; (2) Analisis molekul (103,(115)(116)(117)(118)(119)(120)(121)(122)(123)(124) Ag2SO4, secara 3 dimensi menggunakan Chem 3D. Molekul Ag2SO4 dilukis dengan menggunakan ChemDraw dengan cara memilih Structure dan Convert Name to Structure.…”
Section: Sumberunclassified
“…Molekul Ag2SO4 dibuat dengan menggunakan Chemdraw 2D dan kemudian di pindahkan ke dalam bentuk 3 dimensi menggunakan Chem 3D. Proses ini dapat membantu melihat pola pergerakan molekul (103,(115)(116)(117)(118)(119)(120)(121)(122)(123)(124) secara optimal dan kemungkinan dinamika air selama berinteraksi (164)(165)(166)(167)(168)(169)(170)(171)(172) di lingkungan saat proses splitting berlangsung. Dengan bantuan Chem3D dapat dilihat bentuk surface dari molekul Ag2SO4.…”
Section: Analisis 3d Pada Molekul Ag2so4unclassified